2016
DOI: 10.15294/ujph.v5i4.11372
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Risiko Paparan Pestisida Selama Kehamilan Terhadap Kejadian BBLR Pada Petani Sayur

Abstract: Abstrak ___________________________________________________________________Berat badan lahir rendah (BBLR) menjadi salah satu penyebab utama mortalitas bayi. Permasalahan yang muncul adalah apakah ada hubungan antara paparan pestisida pada masa kehamilan dengan kejadian BBLR di daerah pertanian. Tujuan penelitian ini untuk mengetahui faktor risiko yang berhubungan dengan kejadian BBLR. Penelitian ini merupakanstudi case control. Subjek dibagi menjadi dua kelompok: kelompok kasus sejumlah 25 petani dengan riway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…All mothers who work on agricultural land also do not participate in pest spraying activities, and male farmers carry out these activities. Similar research was also carried out by (Fatmawati, 2016) with p-value = 0.077 14 .…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…All mothers who work on agricultural land also do not participate in pest spraying activities, and male farmers carry out these activities. Similar research was also carried out by (Fatmawati, 2016) with p-value = 0.077 14 .…”
Section: Resultssupporting
confidence: 54%
“…In contrast, acetylcholine plays a role in the activation of thyroid hormones. A pregnant woman with thyroid disorders can interfere with the growth and development of the fetus she contains 14 . Many previous studies have not conducted research related to this.…”
Section: Introductionmentioning
confidence: 99%
“…Even though after categorizing, agricultural activities have proven to be unrelated and are not a risk factor for LBW events, there are types of spraying plants activities that are statistically significant for LBW. The results of a previous study conducted by Fatmawati (2016) showed that risky agricultural activities were associated with LBW events in Ngablak, Magelang (p value = 0.014). The involvement of pregnant women in agriculture consists of various types of work and some of them are directly involved with pesticides, which are activities when women prepare and mix pesticides or spray plants in the fields.…”
Section: Resultsmentioning
confidence: 86%
“…The involvement of pregnant women in agriculture consists of various types of work and some of them are directly involved with pesticides, which are activities when women prepare and mix pesticides or spray plants in the fields. 7 The activity of spraying plants using pesticides was associated with LBW events because these activities have a very high likelihood of being exposed to pesticides. When pregnant women spray the plants, pesticides can enter the body through the respiratory system or skin abortion.…”
Section: Resultsmentioning
confidence: 99%